Implementasi Kurikulum Kontemporer dalam Pendidikan Madrasah Diniah Fathul Ulum di Desa Ngliron untuk Meningkatkan Kompetensi Keagamaan Siswa - Sutikno (https://journal.metanusantara.com/impact/index.php/jpk, 2025)
The low literacy of the Qur'an among junior high school (SMP) students in Indonesia is a crucial issue that requires community-based solutions. This study aims to analyze the level of Qur'an literacy ability of junior high school students in Jati District and evaluate the effectiveness of the implementation of the Magrib Mengaji Program as an effort to strengthen religious literacy. This study uses a Participatory Action Research (PAR) approach with a dual case study design. Primary data sources were obtained from junior high school students as diagnostic test subjects, and key informants including teachers of the Magrib Mengaji Program, mosque administrators, and parent representatives. Data was collected through Qur'anic reading ability tests, in-depth interviews, and participatory observation during the action cycle. Preliminary diagnostic results showed that 45% of students were in the category of reading fluently, indicating a weakness in the existing program's methodology. Through two PAR cycles that focus on interactive teaching methodology training and increasing parental participation, the Maghrib Mengaji Program undergoes a significant transformation. The findings showed that there was an increase in the average Qur'an literacy ability of students by 43% from the initial condition. This improvement proves that collaborative interventions and methodological improvements can fundamentally improve religious literacy competence. The Maghrib Mengaji program has proven to be effective only when implemented with a participatory strategy that empowers the entire community ecosystem.